2015
DOI: 10.1051/bioconf/20150503005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of training needs of winemakers and management systems of the wineries in Armenia

Abstract: Abstract. Armenia has been well known for wine production for many centuries. During Soviet times the industry was particularly specialized in wine, brandy and sparkling wine making. Nearly 25% of brandy produced in the Soviet Union was made in Armenia. After the independence in early 1990s, the industry as a whole collapsed and production volumes declined sharply. Wine industry also shrunk dramatically. During late 90s and early 2000s the sector started to grow slowly. However, the main driver of the sector w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The questions for the expert evaluation were prepared according to the content analysis of available research studies and country reports (Rylko, Khotko, Abuzarova, Yunosheva and Glazunova, 2015;Urutyan, Yeritsyan and Mnatsakanyan, 2015;Syzdykov, Aitmambet and Dautov, 2015;Moroz, Stratan, Ignat and Lucasenco, 2015;Nivievskyi, Stepaniuk, Movchan, Ryzhenkov and Ogarenko, 2015;Khalilov, Shalbuzov and Huseyn, 2015;Bluashvili and Sukhanskaya, 2015;Akhramovich, Chubrik and Shymanovich, 2015), which were presented under the project by expert groups in all analysed countries.…”
Section: Methodsmentioning
confidence: 99%
“…The questions for the expert evaluation were prepared according to the content analysis of available research studies and country reports (Rylko, Khotko, Abuzarova, Yunosheva and Glazunova, 2015;Urutyan, Yeritsyan and Mnatsakanyan, 2015;Syzdykov, Aitmambet and Dautov, 2015;Moroz, Stratan, Ignat and Lucasenco, 2015;Nivievskyi, Stepaniuk, Movchan, Ryzhenkov and Ogarenko, 2015;Khalilov, Shalbuzov and Huseyn, 2015;Bluashvili and Sukhanskaya, 2015;Akhramovich, Chubrik and Shymanovich, 2015), which were presented under the project by expert groups in all analysed countries.…”
Section: Methodsmentioning
confidence: 99%
“…In the past decade, Gil and Carrillo (2016) have noticed the growing consideration and recruitment by Spanish wineries of staff with university degrees specialising in technical careers, in particular oenologists. In contrast, research from Armenia’s wine industry (Urutyan and Yeritsyan, 2015) have identified marginal involvement of management in providing training or educational programs for their staff.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The major part of the production was consumed in Russia and the Soviet Union [21]. Nowadays, the vineyard area stretches over 17,000 ha [22], from which around 2,500 ha are used for winemaking, while the majority (14,500 ha) is still used for brandy and table grape production [23]. The share used for table wine production is stable, but a steady increase in productivity is noticeable [22].…”
Section: Development Of the Armenian Wine Industrymentioning
confidence: 99%
“…In 2017 the situations is mostly unchanged. In total 66,544 farmers cultivate grapes on an average plot size of 0.23 ha [23]. The farmers are still heavily dependent on selling their grapes to the few operating wineries [24].…”
Section: Development Of the Armenian Wine Industrymentioning
confidence: 99%